PROSPECTOR-DEFENDER STRATEGY, AUDITOR INDUSTRY SPECIALIZATION, EARNINGS MANAGEMENT THROUGH REAL ACTIVITIES, AND EARNINGS QUALITY - Andayani, Wuryan; Warsono, Sony (Journal of Indonesian Economy and Business, 2013)
This study observed the influence of the company prospector-defender strategy andÂ auditor industry specialization toward the earnings management through real activitiesÂ and earnings quality. An important finding in this study confirmed that the auditor industryÂ specialization could not restrict the earnings management and the companyâs prospectorÂ strategy could restrict the earnings management. On the contrary, defender strategy couldnot restrict the earnings management. Another finding proved that the auditor industryÂ specialization influence the earnings response coefficient (ERC) and investorsâ response.Besides the auditor industry specialization, as well as the prospector and defender strategies,Â other factors also affected influence ERC are leverage, company size, stock return,Â beta and market return. The interaction among the prospector and defender strategies andÂ unexpected earnings neither influence the CAR nor the investorsâ response. This wasÂ probably because the investors pay attention to the strategy used by the company. However,Â there were any interaction variables: industry specialization auditor, leverage, stockÂ return, beta and market return influence the CAR and investorsâ response.Keywords: auditor industry specialization, prospector-defender strategy, earningsÂ response coefficient, earnings quality.